HUBUNGAN PERILAKU VERBAL ABUSE IBU TERHADAP PERKEMBANGAN PSIKOSOSIAL ANAK USIA PRASEKOLAH - Fitri Anisa; Erika Erika; Widia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The behavior of mather's to their childrens affects the development of children, include the psychosocial development of children. One of the behavior of mather's that have an impact on children's psychosocial development is verbal abuse. Verbal abuse is a set of words or behaviors can hurt other people's feelings that includes insulting with inappropriate words, berating, yelling, scaring, and threatening others. This study aims to determine the relationship between mother's verbal abuse behavior and psychosocial development of preschool in the area of the RI Sidomulyo Public Health Center, Tampan District, Pekanbaru. This study used a descriptive correlation design with a cross sectional approach. The research sample was 98 respondents who were taken using purposive sampling technique with univariate analysis and bivariate analysis using chisquare test. There are 31 (31.6%) respondents with high verbal abuse category who have children in the category of abnormal psychosocial development. The results of statistical analysis showed that there were a significant relationship between mother's verbal abuse behavior on the psychosocial development of preschool with p value (0.000) < alpha (0.05). Mother's verbal abuse behavior has a relationship with the psychosocial development of preschooler. Mothers should improve communication and suggested to have good attitudes to their children and for health care provider to improve health education about verbal abuse behavior to children. Keywords: Preschool, psychosocial development and verbal abuse